Pengaruh Supervisi terhadap Mutu Pendidikan Dasar di Kecamatan Bengkalis Kabupaten Bengkalis - Afandi, Afandi; Daulay, Musnar Indra; Witarsa, Ramdhan (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
Supervision of the sub-district area coordinator in the field of education is one way that can be done to assess the quality of primary education in the area concerned. This research aims to measure how much influence the supervision carried out by the sub-district coordinator has on the quality of primary education in the Bengkalis sub-district, Bengkalis district. The method used in this research is a quasi-experimental method. The results of the research show that the supervision carried out by the sub-district coordinator has a significant effect on the quality of primary education in the Bengkalis sub-district, Bengkalis district. The quality of primary education is reflected in the quality of teachers who are continuing their master's degree in primary education with a total of 23 teachers from the elementary school level and 3 teachers from the junior high school level. Certified teachers should continue their studies to the master level of primary education so that the quality of the teacher concerned can improve and generally improve the quality of primary education in their respective sub-districts.